2012
DOI: 10.1007/s00405-012-2179-0
|View full text |Cite
|
Sign up to set email alerts
|

Ondansetron in patients with tinnitus: randomized double-blind placebo-controlled study

Abstract: The aim of this study was to assess the effect of ondansetron on symptoms of patients with subjective tinnitus accompanied by sensorineural hearing loss or normal hearing. Sixty patients with a chief complaint of tinnitus (with duration of more than 3 months) were equally randomized to ondansetron or placebo for 4 weeks. The dose of ondansetron was gradually increased from 4 mg/day (one tablet) to 16 mg/day (4 tablets) during 12 days and then continued up to 4 weeks. The exact number of tablets was prescribed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…TSI can also assess the magnitude of perceived annoyance and may be more adequate than THI in reflecting the difference between treatment groups. 25 The adequate reliability and validity of VAS, THI and TSI scores have been demonstrated. 17,18,25 VAS and THI are the most commonly accepted and widely used instruments to measure tinnitus.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…TSI can also assess the magnitude of perceived annoyance and may be more adequate than THI in reflecting the difference between treatment groups. 25 The adequate reliability and validity of VAS, THI and TSI scores have been demonstrated. 17,18,25 VAS and THI are the most commonly accepted and widely used instruments to measure tinnitus.…”
Section: Discussionmentioning
confidence: 88%
“…25 The adequate reliability and validity of VAS, THI and TSI scores have been demonstrated. 17,18,25 VAS and THI are the most commonly accepted and widely used instruments to measure tinnitus. 18 Third, a standardized protocol was registered in the PROSPERO database before starting this review, rendering the potential reporting bias of this review as low.…”
Section: Discussionmentioning
confidence: 88%
“…and E.F.) for 3 inclusion criteria: ≥2 independent patient groups treated differently, randomization of patients, and reporting of tinnitus outcomes (if the study examined symptoms other than tinnitus, tinnitus results were reported separately). This yielded 147 studies ( Figure 1) for inclusion in data abstraction and analysis 5–151 …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the antiemetic drug of ondansetron was examined that is expected to be effective against tinnitus and to even improve the hearing threshold, as reported by an ENT team from Teheran [59]. In a randomized, double-blind, and placebo-controlled study, 30 patients with tinnitus persisting for more than 3 months, with and without hearing loss were treated with ondansetron and compared to a placebo group of the same size.…”
Section: Pharmacotherapy Of Tinnitusmentioning
confidence: 99%